2016
DOI: 10.1021/acs.jpcc.5b11229
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Palladium Clusters in an Ionic Liquid: A QM/MM Molecular Dynamics Study

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 72 publications
0
18
1
Order By: Relevance
“…Among the four schemes, CHELPG gave values most consistent with those reported in the literature ,. The CHELPG charges were calculated based on electrostatic potential (ESP) maps and produced by fitting the points around the molecule to provide reasonable atomic partial charges . The calculated and literature values are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Among the four schemes, CHELPG gave values most consistent with those reported in the literature ,. The CHELPG charges were calculated based on electrostatic potential (ESP) maps and produced by fitting the points around the molecule to provide reasonable atomic partial charges . The calculated and literature values are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The 850 cm À1 peak in pure IL shifts to 833 cm À1 (red shift) for AgNPs synthesized in IL. Other peak at 1062 cm À1 in pure IL gets red shifted to1028 cm À1 in Ag-bmimBF4.Obtained product was further characterized by 1 H(Figure S1a, b) and 13 C NMR spectra (Figure S2). No shift in NMR peaks could be observed when a comparison was made between the spectrums of pure IL (Figure S3a, b for 1 H NMR and S4a & S4b for 13 C NMR) and AgNPs prepared in same IL.…”
Section: Spectroscopic Investigationsmentioning
confidence: 96%
“…Other peak at 1062 cm À1 in pure IL gets red shifted to1028 cm À1 in Ag-bmimBF4.Obtained product was further characterized by 1 H(Figure S1a, b) and 13 C NMR spectra (Figure S2). No shift in NMR peaks could be observed when a comparison was made between the spectrums of pure IL (Figure S3a, b for 1 H NMR and S4a & S4b for 13 C NMR) and AgNPs prepared in same IL. This confirms that Ag cluster is surrounded only by anions but not by cations, as reported earlier also [28,29].…”
Section: Spectroscopic Investigationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Heinz and co-workers systematically evaluated abstraction energies of Pd atoms from Pd NPs containing up to 1000 atoms. 137 Zvereva and co-workers found that ILs stabilised Pd clusters through strong polarization interactions, 175 and they further demonstrated that the leaching of Pd atoms can occur via ionic [PdX] species rather than via "naked" atoms. 176 Catalytic ensembles involving molecular and surface active species are indeed dynamic, 177 and both homogeneous and heterogeneous cycles can co-exist via oxidative leaching and deposition processes.…”
Section: Deactivation Pathwaysmentioning
confidence: 99%